Effects of triploid induction on innate immunity and hematology in Astyanax altiparanae - Levy-Pereira, Nycolas [UNESP]; Carriero, Mateus Maldonado; Yasui, George Shigueki; Meira, Caroline Munhoz; de Sousa, Ricardo Luiz Moro; Maia, Antônio Augusto Mendes; Senhorini, José Augusto; Pilarski, Fabiana (Elsevier, 2021)
Triploid induction is a promising biotechnique that could be used to enhance aquaculture yields in the near future. However, studies conducted with several fish species have demonstrated that the presence of an extra set of chromosomes may result in deleterious health effects. Furthermore, studies of fish immune responses still need to be conducted before these specimens can be readily commercialized. In the study presented herein, we evaluated the effects of triploid induction on hematology, erythrocyte morphometry and morphology, phagocytosis, and the expression levels of IL-1β and TGF-β using specimens of the Neotropical species, Astyanax altiparanae. In general, the cell counts of erythrocytes, leukocytes, and neutrophils in triploid fish were lower than those in diploid fish. The erythrocytes of triploid fish were larger than those found in diploid fish, but also demonstrated considerably higher frequencies of cellular and nuclear abnormalities. Although not statistically significant, triploid induction resulted in a phagocytic capacity (PC) 20% lower than that found with diploid fish. No notable differences were observed in phagocytic index (PI). Gene expression levels for the cytokine IL-1 were lower in tissues from the head kidney, liver, and spleen of triploid fish with respect to diploid fish. Gene expression levels of TGF-β were lower only in the spleen of triploids compared to diploids. In conclusion, triploid induction resulted in A. altiparanae specimens with immune impairments and potentially lower resistances to disease and low-quality environments.
Keywords: Cytokines; Erythrocytes morphometry; Hematology; Phagocytosis; Triploid induction; Yellow-tail tetra